Pengaruh Produk Domestik Regional Bruto dan Variabel Kepariwisataan Terhadap Lingkungan Hidup di Provinsi Destinasi Wisata Prioritas di Pulau Jawa - Laura, Gabriella Deby; Suhartini, Atik Maratis (Seminar Nasional Official Statistics, 2023)
Tourism has the potential to become a mainstay sector in increasing the economy, so the government settings 10 priority destinations in Indonesia. Positive tourism development is marked by increased visitor, but if we don't pay attention to the environment quality index (IKLH), it will have a negative impact on human survival. Java Island receives the largest foreign investment compared to outside Java Island, so it’s suspected has greater potential of environmental damage. This study to know the effect of Gross Regional Domestic Product (GRDP) and tourism on the IKLH in priority destinations on Java Island in 2011-2021 using the panel data regression. The result shows that GRDP and average length of stay (RLM) have a positive significant effect on IKLH, because Indonesia has implemented green hotels and ecotourism. Meanwhile, the occupancy rate (TPK) has a significant negative effect on IKLH, because a high TPK means more tourists and energy consumption.